PENETAPAN NILAI ACUAN AMILOSA BEBERAPA VARIETAS PADI MENGGUNAKAN METODE PENGIKATAN IODIN (I): KALIUM IODIDA (KI) MELALUI UJI BANDING ANTARLABORATORIUM - Shinta D. Ardhiyanti; Udin S. Nugraha; Siti Dewi Indrasari; Bram Kusbiantoro (Pusbindiklat - LIPI, 2014)
The assigned value of amylose content in rice is the key factor in the development of internal laboratory quality control system. To produce reliable data, quality control system becomes necessary. The aim of this research was to determine the assigned value of amylose content of several rice varieties through interlaboratory testing. This research was conducted in 2012 in Post-Harvest Physiology Laboratory of Indonesian Center for Rice Research (ICRR) and several laboratories in Bogor, West Java, as interlaboratory testing participant. Samples used in this research were 4 new superior varieties with different amylose content i.e. Lusi, Sintanur, Ciherang, and Inpari 12, and had been confirmed for their homogenity and stability. The Cochran’s, the Grubbs’, and the Z-score tests were used to determine the outlier data of the interlaboratory testing results and the competent laboratories as well. The assigned values obtained for each variety were Lusi 6.29% (±1.73); Sintanur 19.42% (±1.51); Ciherang 23.78% (±1.44); and Inpari 12 29.83% (±0.68). All tested varieties could be used as reference materials in determining the laboratory performance to analyze rice’s amylose content using iodine: potassium iodide (I:KI) binding method.